Implementation of ESG Principles as a Corporate Sustainability Strategy: A Literature Study - Nasywa A, Cailah; Putri, Icha Aulia; Basjah, Fabiola Latifah; Aini, Nabilah Qurrotul; Mushfiroh, Luluk; Rachmawati, Titiek (Indonesian Journal Publisher, 2025)
Companies are driving a shift in the global business paradigm to not only achieve financial benefits, but also pay attention to social and ecological responsibilities as part of their sustainability strategy. The principles of environment, social issues, and governance (ESG) are the main settings for assessing and managing non-financial effects that affect a company's services and reputation. The purpose of this study is to investigate the implementation of ESG as a sustainability strategy for companies through literature research from various academic sources and business reports. The results of this study indicate that the implementation of ESG offers significant benefits, including increased operational efficiency, fame, funding, and competitiveness. However, Indonesian companies still face challenges, including limited resources, lack of understanding of management, and integrated reporting standards. This study confirms that the integration of ESG into business strategy is not only a moral and regulatory requirement, but also a competitive advantage in addressing global dynamics, and supporting the achievement of the Sustainable Development Goals (SDGs).